Characteristics of temporal changes and influencing factors of carbon dioxide and methane fluxes at the water-gas interface of the Inner Mongolia section of the Yellow River - Aruhan; Xia Wu; Wuyinga; Hongxia Bao; Yue Lang; Narentuya; Fang Liu; Liming Qi; Xiaoli Wang (Journal of Freshwater Ecology)
Global warming has evolved into a global environmental concern. Despite the significant impact of rivers on greenhouse gas (GHG) emissions, there remains a lack of wide quantification of emissions at high temporal resolution. This research investigated the characteristics of the CO2 exchange flux (FCO2) and CH4 exchange flux (FCH4) at the interface of water and gas, as well as the primary determinants that impact these fluxes, at both the seasonal and 24-h scales, in the Inner Mongolia section of the Yellow River (IMYR). FCO2 was 52.52 ± 78.26 mmol·m−2·d−1 in summer, which was higher than autumn (30.81 ± 51.24 mmol·m−2·d−1) and spring (-96.09 ± 264.31 mmol·m−2·d−1). FCH4 peaked in summer (928.45 ± 513.31 μmol·m−2·d−1) and declined in the fall (326.76 ± 576.31 μmol·m−2·d−1). The lowest FCH4 was recorded in spring (61.75 ± 190.26 μmol·m−2·d−1). Wind speed (WS) and organic carbon mineralisation were the primary determinants of FCO2 at the seasonal scale, whereas temperature and dissolved oxygen (DO) were the primary determinants of FCH4. Monitoring FCO2 and FCH4 at night revealed higher average levels than during the day. FCO2 was regulated by levels of dissolved inorganic carbon (DIC) and total phosphorus (TP) levels over a 24-h period, whereas FCH4 was regulated by levels of dissolved oxygen (DO) and total nitrogen (TN). Throughout the majority of the time period, the IMYR river segment emits carbon dioxide (CO2) and methane (CH4) to the atmosphere. Due to the fact that emission patterns and driving mechanisms of riverine CO2 and CH4 differ across time scales, it is necessary to conduct more precise observations with high spatial and temporal resolution in order to acquire the most reliable data and comprehend more targeted approaches to carbon emission reduction.